6x-(7-4x)+12=7x-(8+6x)+9-3x-4-(8x-12)

Simple and best practice solution for 6x-(7-4x)+12=7x-(8+6x)+9-3x-4-(8x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(7-4x)+12=7x-(8+6x)+9-3x-4-(8x-12) equation:



6x-(7-4x)+12=7x-(8+6x)+9-3x-4-(8x-12)
We move all terms to the left:
6x-(7-4x)+12-(7x-(8+6x)+9-3x-4-(8x-12))=0
We add all the numbers together, and all the variables
6x-(-4x+7)-(7x-(6x+8)+9-3x-4-(8x-12))+12=0
We get rid of parentheses
6x+4x-(7x-(6x+8)+9-3x-4-(8x-12))-7+12=0
We calculate terms in parentheses: -(7x-(6x+8)+9-3x-4-(8x-12)), so:
7x-(6x+8)+9-3x-4-(8x-12)
determiningTheFunctionDomain 7x-(6x+8)-3x-(8x-12)+9-4
We add all the numbers together, and all the variables
4x-(6x+8)-(8x-12)+5
We get rid of parentheses
4x-6x-8x-8+12+5
We add all the numbers together, and all the variables
-10x+9
Back to the equation:
-(-10x+9)
We add all the numbers together, and all the variables
10x-(-10x+9)+5=0
We get rid of parentheses
10x+10x-9+5=0
We add all the numbers together, and all the variables
20x-4=0
We move all terms containing x to the left, all other terms to the right
20x=4
x=4/20
x=1/5

See similar equations:

| 2(2x+3)+2(2x+3)=0 | | 7x=2640 | | -9x-(8x+7)=9x-(-7+6x) | | 6=0.06*100+b | | 4x+5)=(x^2-27 | | 1778=3x-150 | | X+3x+x-2=78 | | (2x+10)(2x-50)(x-40)=180 | | 50+-1x=x+66 | | 6(2x+4=(3x+6 | | 1)y+6=20 | | T=4s+4.03 | | T=4s+4.03s | | 220.00+0.15m=299.50 | | 8(x-5)+29=7x-6 | | 8(x-2)+3=8x-12 | | 6(x-8)+40=6x-8 | | -10−4g=-6g | | 18x−3x^2=0 | | -7v+3=-7−6v | | -5k=-7k−10 | | X(x-1)=200 | | 2−7u=-5u+6 | | 7r+21=44r | | 5r+10=-5+2r | | 29=257-x | | 4k+10=5k | | 10r=8+8r | | 14+25f=35+16f | | -12p39=11(p+14) | | -2−6v=-5v | | (d/5)+3D-10=(1/3)d+33 |

Equations solver categories